Updated peer review of the pesticide risk assessment of the active substance cyazofamid. (4th September 2020) - ,; Anastassiadou, Maria; Arena, Maria; Auteri, Domenica; Brancato, Alba; Bura, Laszlo; Carrasco Cabrera, Luis; Chaideftou, Eugenia; Chiusolo, Arianna; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State, France, and co‐rapporteur Member State, Latvia, for the pesticide active substance cyazofamid are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of cyazofamid as a fungicide on potato, tomato and cucurbits and were updated for non‐target organisms. The reliable end points, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.